Metaformosis Pemikiran Intelektual Muda NU: Suatu Pandangan dari Outsider NU - Kamaruzzaman Bustaman Ahmad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2004)
This paper tries to elaborate how the role of youth of NU in Indonesia Islamic thought. The main focus of this paper is the intellectual tradition young generation of NU The 2000s constitute the years where the youth of NU stay in everywhere and influenced the life of Indonesia intellectuality. The writer argues that there are some factors in the genealogy of their thought: First, Islamic boarding school as the central of intellectual tradition of NU; Second, the NGO's working; Three, the scientific networking from Egypt Four, The State Institute of Islamic Studies (IAIN) as the place that did not make their intellectual satisfactory. They look for the other activity; Five, the influence of contemporary Islamic thought whose tends radically and left; Six, the relation with the Indonesians; Seven, the figure of Gus Dur as the protector for them in their liberal idea.